Design and Testing of MEMS Component for Electromagnetic Pulse Protection - Shiyi Li; Hengzhen Feng; Wenzhong Lou; Yuecen Zhao; Sining Lv; Wenxing Kan (Sensors)
With the demand for high-safety, high-integration, and lightweight micro- and nano-electronic components, an MEMS electromagnetic energy-releasing component was innovatively designed based on the corona discharge theory. The device subverted the traditional device-level protection method for electromagnetic energy, realizing the innovation of adding a complex circuit system to the integrated chip through micro-nanometer processing technology and enhancing the chip’s size from the centimeter level to the micron level. In this paper, the working performance of the MEMS electromagnetic energy-releasing component was verified through a combination of a simulation, a static experiment, and a dynamic test, and a characterization test of the tested MEMS electromagnetic energy-releasing component was carried out to thoroughly analyze the effect of the MEMS electromagnetic energy-releasing component. The results showed that after the strong electromagnetic pulse injection, the pulse breakdown voltage of the MEMS electromagnetic energy-releasing component increased exponentially in terms of the pulse injection voltage, and the residual pulse current decreased significantly from one-third to one-half of the original, representing a significant protective effect. In a DC environment, the breakdown voltage of the needle–needle structure of the MEMS electromagnetic energy-releasing component was 144 V, and the on-time was about 0.5 ms.